1989
DOI: 10.1002/macp.1989.021900405
|View full text |Cite
|
Sign up to set email alerts
|

Activation of propene polymerization by hydrogen for improved MgCl2‐supported Ziegler‐Natta catalysts

Abstract: As in the case of the third generation MgCl,-supported stereospecific catalysts, characterized by the use of aromatic esters as internal and external Lewis bases, the new improved family of catalysts, containing an aromatic diester as internal Lewis base and a trialkoxyphenylsilane as external Lewis base, was found to be sensitive to hydrogen. A very strong activation effect, followed by deactivation, was observed upon introduction of small amounts of hydrogen. In the present case the effect is reversible, unl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 7 publications
2
16
0
Order By: Relevance
“…The majority of the rate boost occurs at as little as 1 mol % hydrogen. This effect is also reversible, as noted by others 24. Figure 11(b) shows an experiment where the catalyst was prepolymerized with propylene as described earlier, the propylene was removed, and the reactor was flushed with nitrogen.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…The majority of the rate boost occurs at as little as 1 mol % hydrogen. This effect is also reversible, as noted by others 24. Figure 11(b) shows an experiment where the catalyst was prepolymerized with propylene as described earlier, the propylene was removed, and the reactor was flushed with nitrogen.…”
Section: Resultssupporting
confidence: 58%
“…Their work indicates initial propylene rate can be boosted by a factor of 2.5 as hydrogen partial pressure is increased. Yuan et al,31 Choi and Ray,32 and Spitz et al24 have found that although hydrogen at low concentrations causes a rate increase, higher hydrogen levels lower activity and increase deactivation. The effect of hydrogen addition on propylene polymerization was found to be reversible, and no effect on ethylene rate was noted.…”
Section: Resultsmentioning
confidence: 98%
“…A higher amount of hydrogen in a PP plant reactor usually decreases its throughput level, because hydrogen decreases heat removal efficiency as well as monomer partial pressure. A state‐of‐the‐art catalyst design with an ideal balance between isospecificity and hydrogen response still remains a challenging target, due to poor understanding of the specific mechanism of the chain‐transfer reaction by hydrogen 8–13. Some traditional kinetic investigations have shown that the molecular weight of polymer decreases proportionally to the square root of the partial pressure of hydrogen, suggesting that hydrogen might act as a chain‐transfer agent solely in the atomic state after dissociation 14–16…”
Section: Introductionmentioning
confidence: 99%
“…The most important step for the preparation of spherical catalyst particles is the support preparation step. This new generation of catalysts often utilizes organic diester as internal donor and silane as external donor 10, 13. This research focuses on the preparation of MgCl 2· ID · TiCl 4· ED catalysts with controlled morphology from MgCl.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of the catalyst was evaluated in slurry using triethylaluminum (AlEt 3 ) as a cocatalyst. Previously, some articles have been reported on the some effective parameters on the catalyst support morphology and polymerization conditions on the polymer morphology 13–20. In this article, the effects of media viscosity, mixing speed, and injection time on the morphology of the catalyst support in two different conditions (with emulsifier and without it) were investigated.…”
Section: Introductionmentioning
confidence: 99%